Gender differences in chronic lower limb ischemia presentation and revascularization outcomes - Correia,Ricardo (2021)
Abstract Introduction: Sex-specific data on outcomes after lower limb revascularization associate the female gender with worse surgical outcomes, particularly after open procedures. Women were found to be more likely to suffer from procedure complications, limb loss, and mortality than their male counterparts. This study aims to identify differences in demographic characteristics, clinical presentation and all major outcomes after lower limb revascularization between female and male patients. Methods: This retrospective, single-center study comprises all never-revascularized lower limbs in patients with clinically diagnosed PAD who underwent a lower limb therapeutic vascular intervention in a tertiary hospital between January 2017 and December 2018. Women's limbs Group (F) was compared against men's limbs Group (M). The primary endpoint was major amputation, and the secondary endpoints were restenosis/occlusion, vascular reintervention and overall survival. Subgroup analysis was undertaken considering open, endovascular or hybrid procedures. Results: Group M included 324 male lower limbs; patients had a mean age of 67,5 years. Group F included 96 female lower limbs; patients had a mean age of 71,7 years (p<0,001). There were no significant differences in cardiovascular risk factors between groups, aside from a higher prevalence of smoking in Group M and hypertension in Group F (p<0.001). 83% of Group F procedures and 79% of procedures in Group M were performed due to CLTI (p=0,321). We found no statistically significant difference between groups regarding wound or infection grading (WIfI) and femoropopliteal or BTA anatomic disease staging (GLASS). Group M was more likely to have aortoiliac (p=0,014) and common femoral artery disease (p=0.001), and Group F to have more severe BTK disease (p=0,012). Group F had a higher proportion of endovascular procedures (p<0.001). Amputation rates in Group M and Group F were 8±2% and 7±3% at 1 month, 14±2% and 16±4% at 1 year, 15±2% and 19±4% at 2 years, respectively (p=0,564). There were no significant differences in rates of procedure restenosis/occlusion between groups (p=0,395). Reintervention rates in Group M and Group F were 13±2% and 13±3% at 1 month, 21±2% and 20±4% at 1 year, 25±3% and 24±5% at 2 years, respectively (p=0,74). Overall survival in Group M and Group F was 97±1% and 93±3% at 1 month, 84±2% and 84±4% at 1 year, 77±3% and 72±5% at 2 years, respectively (p=0,443). Stratifying according to the type of vascular procedure (open, endovascular or hybrid), we found no significant difference between groups in the outcomes mentioned above. Conclusion: Overall, women were more likely to be older, to have more severe BTK disease, and to undergo endovascular procedures. However, this study suggests no major differences in limb outcomes for women who undergo lower limb revascularization procedures.